Konstruksi Teori Pendidikan Berbasis Filsafat Jawa Kuno - Purwo Susongko (Universitas Pancasakti Tegal, 2019)
This research aims to compile the philosophical formulation and construction of educational theory based on the ancient Javanese philosophy book, Sang Hyang Tatwa Jnana and Sang Hyang Nawa Ruci. To achieve these research objectives, carried out by studying and compiling philosophical formulations and educational theories that originate from ancient Javanese philosophy. This research uses document analysis method. The documents used are the books of Sang Hyang Tatwajnana and Sang Hyang Nawa Ruci, which were compiled and reinterpreted by Damar Shashangka in his book entitled Ancient Javanese Science. Ancient Javanese Theory of Education can be formulated as follows: (1) the general purpose of education is to release egoism, greed, and hatred, (2) Students have potential abilities derived from experiences gained from previous births (reincarnations), (3) Contents education is divided into two, namely soft skills and hard skills. Soft skill is learning related to awareness, perception and affective while hard skills are related to cognitive and psychomotor abilities to support the fulfillment of life needs, (4) The ideal teacher in general is a person who has reached maturity marked by Satva character (stable and calm), ( 5) Learning strategies based on the use of meditation to improve concentration of learning, (6) There are 5 dimensions that must be developed in the educational process namely awareness, perception, cognitive, affective and psychomotor.